A Mechanism of methods used when working with documents and processing documents using artificial intelligence: Image recognition working mechanism - Saktashova, Umit (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2022)
Automation of the processes of analysis, processing and transmission of information in the development of information systems reduces the complexity of implementation, time and material costs, frees up the resources of developers to solve more complex and creative tasks. The transition of document management now to electronic document management technologies not only dramatically accelerates the speed of business processes of companies, but also provides cost savings when abandoning paper media, to minimize most operations when processing electronic documents, the use of artificial intelligence technologies is considered effective. In the article I will consider the possibilities of artificial intelligence technologies used in the process of enterprises, in converting documents into electronic and in the exchange of electronic documents. Depending on the structure of the text, the review of the applied methods of artificial intelligence, neural networks and the analysis of their work processes is carried out. Depending on the structure of the document, neural networks are used. Various recognition methods can be used for image recognition according to the characteristics of the recognized characters. The article describes the mechanism of image recognition, the document processing process, the operation of NLP algorithms. Processing documents of a professional organization with the help of artificial intelligence used in it improves the quality of the document flow of the enterprise, leads to time savings and cost reduction.